(untitled) (Research, Society and Development, 2020)
Ice conservation stands out as one of the most economical, simple and suitable ways to maintain the freshness of the fish. The study evaluated the microbiological alterations of the eviscerated and uneviscerated Genyatremus luteus, stored in ice, through organoleptic analyzes by the Quality Index Method (MIQ) and the presence of total, thermotolerant coliforms and psychrotrophic bacteria. For the microbiological analysis, 18 fish samples were collected, 9 eviscerated and 9 uneviscerated from three free markets of São Luís, during October and November 2019. Analyzes were performed on days one, four and seven to evaluate the potential of ice to maintain the freshness of the fish. The uneviscerated fish presented the highest index of microorganisms and psychotropic bacteria, where the fair B stood out for the highest values, and the initial number of total coliforms from the first to the seventh day were 15.0 NMP/g, 240 NMP/g and 1x10³ NMP/g. For thermotolerant microorganisms it started with 15NMP/g, 460 NMP/g and 460 NMP/g. psychrophilic bacteria also formed a larger number of colonies in uneviscerated fish, with 1.68x105 CFU / g at 10-2 dilution and 4.92x105 CFU / g at 10-3 dilution on day one and day 4.47x105 CFU/g at 10-2 and 1.48x106 UFC/g at 10-7 the seventh-day plaque analysis was considered “untold”. With the study we observed that the fish preserved in ice, gutted, maintained its microbiological quality suitable for consumption until the seventh day and the proper freshness also for seven days.